Effects of Self‐Concept on Restoring a Positive Motivational State After an Exam‐Like Situation. Issue 1 (14th November 2019) - Wimmer, Sigrid; Paechter, Manuela; Lackner, Helmut K.; Papousek, Ilona
ABSTRACT: Exams often trigger avoidance motivation and a tendency to withdraw; instead, an approach‐oriented motivational state would be more desirable, since this encourages an invigorated and persistent approach to tasks. This study investigated the role of academic self‐concept on the activation of relative approach versus avoidance motivation during the course of an exam‐like situation. In 62 university students (50 women), academic self‐concept was assessed using self‐ratings, and activation of approach versus avoidance motivation was assessed by using the electroencephalogram alpha asymmetry response. Academic self‐concept proved to be an important moderator of motivational responses during the challenging situation. A more negative self‐concept was related to sustained decrease in approach motivation, to rumination, and to worsened mood. In contrast, a positive self‐concept was related to more positive mood and activation of approach motivation even beyond task completion. The findings have educational implications, for instance, for the design of exams and performance feedback.